2014
DOI: 10.1186/s40557-014-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead levels of Korean lead workers in 2003–2011

Abstract: ObjectivesThis study aimed to document the trend in blood lead levels in Korean lead workers from 2003 until 2011 and blood lead levels within each of the main industries.MethodsNine years (2003–2011) of blood lead level data measured during a special health examination of Korean lead workers and collected by the Korea Occupational Safety and Health Agency were analyzed. Blood lead levels were determined by year, and a geometric mean (GM) was calculated for each industry division.ResultsThe overall GM blood le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…Lead level is not the same in different countries: Poland (154.8 µg/dl), Ethiopia (40 µg/dl), Pakistan (10 -60 µg/dl), and Korea (4.35 µg/dl). This diversity may be due to the type of job, safely level, and development level of the country (37)(38)(39)(40). Studies show that the situation is worse in developing countries (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead level is not the same in different countries: Poland (154.8 µg/dl), Ethiopia (40 µg/dl), Pakistan (10 -60 µg/dl), and Korea (4.35 µg/dl). This diversity may be due to the type of job, safely level, and development level of the country (37)(38)(39)(40). Studies show that the situation is worse in developing countries (36).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies demonstrated that there is a direct relationship between mean BLL, mean work experience of workers, and mean age of workers; that is, as workers become older and get more experienced, lead level increases in their blood (39,40). Lack of a significant relationship in our study may be due to the minimal difference between mean work experience and the mean age of workers who participated in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the National Longitudinal Study of Adolescent Heath, suicide attempt was linearly associated with income (p<0.1) in American adolescents [ 34 ]. The geometric means of BLL were higher in the “Manufacture of Electrical Equipment” including lead storage batteries and in the “Manufacture of Rubber and Plastic Products” including the process of manually mixing stabilizers while manufacturing Poly Vinyl Chloride products than in other divisions in Korea [ 35 ]. High lead exposure is more likely to occur in small plants where the workplace tends to be more poorly controlled compared to large plants [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these linear regression models were examined at the BLL-3 µg/dL threshold level in order to have a larger sample size for the exposed population and have more robust regression models. The 3 µg/dL threshold has been demonstrated to cause worse health outcomes in several studies [41][42][43]. The data were adjusted for age, gender, BMI, ethnicity, alcohol consumption, and smoking based on the literature [44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%